ASSESSMENT OF THE KNOWLEDGE AND ATTITUDE OF SAUDI POPULATION ABOUT ORGAN DONATION (Applied Biological Research, 2024)
Organ donation is a charitable act that saves lives by addressing organ failure. This study aimed to assess the knowledge and attitude of the Saudi population regarding organ donation. A descriptive community-based study was conducted across the Kingdom of Saudi Arabia (KSA), targeting Saudi males and females aged 18 to 60 years from different regions. Data were collected from 702 participants using an online questionnaire.Among the respondents, 83.5% (586) were aged 18-30 years, 90% (632) were females, and 67.9% (477) were from the Western region. Social media was the most common source of organ donation information (88.2%), followed by family and friends. Only 14 participants (2%) reported having donated organs, while 17.8% (125) had registered as organ donors. Knowledge about organ donation was limited: 21.1% knew that organ transplantation can be performed at any age, and 55.4% were aware that Islam permits organ donation.
Keywords: Attitude; knowledge; organ donation; Saudi population